Whole-Genome Sequences of Five Acinetobacter baumannii Strains From a Child With Leukemia M2 - Mancilla-Rojano, Jetsi; Castro-Jaimes, Semiramis; Ochoa, Sara A.; Bobadilla del Valle, Miriam; Luna-Pineda, Victor M.; Bustos, Patricia; Laris-González, Almudena; Arellano-Galindo, José; Parra-Ortega, Israel; Hernández-Castro, Rigoberto; Cevallos, Miguel A.; Xicohtencatl-Cortes, Juan; et al. (Frontiers in Microbiology, 2019)
Acinetobacter baumannii is an opportunistic pathogen and is one of the primary etiological agents of healthcare-associated infections (HAIs). A. baumannii infections are difficult to treat due to the intrinsic and acquired antibiotic resistance of strains of this bacterium, which frequently limits therapeutic options. In this study, five A. baumannii strains (810CP, 433H, 434H, 483H, and A-2), all of which were isolated from a child with leukemia M2, were characterized through antibiotic susceptibility profiling, the detection of genes to encode carbapenem hydrolyzing oxacillinases, pulsed-field gel electrophoresis (PFGE), multilocus sequence typing (MLST), adherence and invasion assays toward the A549 cell line, and the whole genome sequence (WGS). The five strains showed MDR profiles and amplification of the blaOXA-23 gene, belonging to ST758 and grouped into two PFGE clusters. WGS of 810CP revealed the presence of a circular chromosome and two small plasmids, pAba810CPa and pAba810CPb. Both plasmids carried genes encoding the Sp1TA system, although resistance genes were not identified. A gene-by-gene comparison analysis was performed among the A. baumannii strains isolated in this study and others A. baumannii ST758 strains (HIMFG and INCan), showing that 86% of genes were present in all analyzed strains. Interestingly, the 433H, 434H, and 483H strains varied by 8-10 single nucleotide variants (SNVs), while the A2 and 810CP strains varied by 46 SNVs. Afterward, an analysis using BacWGSTdb showed that all of our strains had the same resistance genes and were ST758. However, some variations were observed in relation to virulence genes, mainly in the 810CP strain. The genes involved in the synthesis of hepta-acylated lipooligosaccharides, the pgaABCD locus encoding poly-β-1-6-N-acetylglucosamine, the ompA gene, Csu pili, bap, the two-component system bfms/bfmR, a member of the phospholipase D family, and two iron-uptake systems were identified in our A. baumannii strains genome. The five A. baumannii strains isolated from the child were genetically different and showed important characteristics that promote survival in a hospital environment. The elucidation of their genomic sequences provides important information for understanding their epidemiology, antibiotic resistance, and putative virulence factors.